2006
DOI: 10.1016/j.asj.2006.04.001
|View full text |Cite
|
Sign up to set email alerts
|

Long-term safety and efficacy of polyurethane foam-covered breast implants

Abstract: Polyurethane foam-covered implants result in long-term reduction in the risk of capsular contracture and appear to have a safety profile similar to other silicone gel-filled devices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
44
1
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 85 publications
(47 citation statements)
references
References 38 publications
1
44
1
1
Order By: Relevance
“…In disagreement with previously mentioned data, Disa suggested the presence of risk factors for infections in tissue expanders, such as for instance, adjuvant CT and smoking [28]. Actually, as shown by our study and by Handel et al, infections rate with polyurethane implants was still lower (1.9%) than infections rate with textured implants (2.8%) [29]. Based on these data, it appears infections rate was not associated with the type of implant surface, but it appears to be perfectly comparable to any other type of implant.…”
Section: Resultscontrasting
confidence: 75%
See 1 more Smart Citation
“…In disagreement with previously mentioned data, Disa suggested the presence of risk factors for infections in tissue expanders, such as for instance, adjuvant CT and smoking [28]. Actually, as shown by our study and by Handel et al, infections rate with polyurethane implants was still lower (1.9%) than infections rate with textured implants (2.8%) [29]. Based on these data, it appears infections rate was not associated with the type of implant surface, but it appears to be perfectly comparable to any other type of implant.…”
Section: Resultscontrasting
confidence: 75%
“…It appeared that skin rash would be triggered by tissue reaction with polyurethane surface. In the most recent study published by Händel in 2006, different data have been analysed comparing either polyurethane and textured implants, both were used either in cosmetic and reconstruction surgery [29]. In 107 breast reconstructions using polyurethane, complications were reported in 8.4% of patients in total: hematoma, 2.3%; infections, 1.9%; implant rupture, 1.4% and capsular contracture, 2.8%.…”
Section: Resultsmentioning
confidence: 98%
“…At 8 months after the procedure, the breasts of the study group (with polyurethane-covered implants) were softer and less likely to form a capsular contracture than the implants in patients that had a texturized surface. On the other hand, except for a transient and self-limited rash, no evidence has shown that polyurethane implants present more complications than texturized or smooth gel implants [19].…”
mentioning
confidence: 99%
“…The biological system represents a hostile environment to the polymer thus poly ether systems are oxidised it would seem by reactive oxygen species generated from adherent macrophages and foreign body giant cells (Christenson, Wiggins et al, 2004). The reactive oxygen radicals then react at the carbon adjacent to the oxygen creating a site for crosslinking or subsequent chain scission (Handel and Gutierrez, 2006). In this case the ether oxygen provides additional stability to the unpaired electron by virtue of its lone pairs [ Fig.…”
Section: Biodegradationmentioning
confidence: 99%
“…This material was particularly chosen because it reduced the problem of ''capsular contracture'', a common complication in breast augmentation surgery where tissue forming around the implant Fig. 3.12 Covalent attachment of Heparin onto the surface of a polyurethane elastomer contracts and causes the implant to appear hardened (Handel and Gutierrez, 2006). It was found that on removal of the implants substantial amounts of the polyurethane material was missing (Slade 1982) this led to concerns that the degradation of the polyurethane in these materials could release substantial amounts of toluene diisocyanate, a potential carcinogen.…”
Section: Biodegradationmentioning
confidence: 99%